2016
DOI: 10.1021/acs.inorgchem.6b01056
|View full text |Cite
|
Sign up to set email alerts
|

Cohesive Energies and Enthalpies: Complexities, Confusions, and Corrections

Abstract: The cohesive or atomization energy of an ionic solid is the energy required to decompose the solid into its constituent independent gaseous atoms at 0 K, while its lattice energy, Upot, is the energy required to decompose the solid into its constituent independent gaseous ions at 0 K. These energies may be converted into enthalpies at a given temperature by the addition of the small energies corresponding to integration of the heat capacity of each of the constituents. While cohesive energies/enthalpies are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 32 publications
(28 reference statements)
1
13
0
Order By: Relevance
“…Recent studies of the magneto-ionic properties of single-layer thin films with structural oxygen (Co 3 O 4 ) or nitrogen (CoN) ions, present in the as-prepared thin-film state, have demonstrated that fully reversible and cyclable magnetic transitions between a nonferromagnetic (OFF) and a ferromagnetic state (ON) are indeed possible. ,, Interestingly, and in contrast to the diffusion channels observed in Co 3 O 4 , CoN films transport nitrogen via a planar ion migration front and possess both superior cyclability and lower operating voltages than Co 3 O 4 , hinting that metal nitrides may compare favorably with their metal oxide counterparts. Previous ab initio calculations of the enthalpy of formation of CoN have predicted values of ΔH f ≈ −50 kJ mol –1 , significantly higher (i.e., less negative) than experimental estimates conducted on CoO and Co 3 O 4 of ΔH f ≈ −237.9 and −910.02 kJ mol –1 , respectively. This is consistent with the difference in electronegativity between nitrogen and oxygen: the lower electronegativity of nitrogen results in weaker bonds with Co cations, suggesting increased magneto-ionic mobility. Properly tuned FeN may be a tantalizing alternative target material for magneto-ionics, as ab initio calculations show that the enthalpy of formation of FeN is comparable to that of CoN and significantly higher (i.e., less negative) than that of FeO. , In addition, magnetic nitrides , such as Fe–N have recently drawn significant research interest due to their array of desirable properties, including high hardness, melting point, incompressibility, cost efficiency, and greater magnetization than iron oxides, another class of magneto-ionic target materials. ,, Iron nitrides also span a wide range of mechanical and magnetic properties, which can be tuned by varying the nitrogen concentration in Fe x N y , and can be easily integrated with semiconductor electronics.…”
Section: Introductionsupporting
confidence: 70%
“…Recent studies of the magneto-ionic properties of single-layer thin films with structural oxygen (Co 3 O 4 ) or nitrogen (CoN) ions, present in the as-prepared thin-film state, have demonstrated that fully reversible and cyclable magnetic transitions between a nonferromagnetic (OFF) and a ferromagnetic state (ON) are indeed possible. ,, Interestingly, and in contrast to the diffusion channels observed in Co 3 O 4 , CoN films transport nitrogen via a planar ion migration front and possess both superior cyclability and lower operating voltages than Co 3 O 4 , hinting that metal nitrides may compare favorably with their metal oxide counterparts. Previous ab initio calculations of the enthalpy of formation of CoN have predicted values of ΔH f ≈ −50 kJ mol –1 , significantly higher (i.e., less negative) than experimental estimates conducted on CoO and Co 3 O 4 of ΔH f ≈ −237.9 and −910.02 kJ mol –1 , respectively. This is consistent with the difference in electronegativity between nitrogen and oxygen: the lower electronegativity of nitrogen results in weaker bonds with Co cations, suggesting increased magneto-ionic mobility. Properly tuned FeN may be a tantalizing alternative target material for magneto-ionics, as ab initio calculations show that the enthalpy of formation of FeN is comparable to that of CoN and significantly higher (i.e., less negative) than that of FeO. , In addition, magnetic nitrides , such as Fe–N have recently drawn significant research interest due to their array of desirable properties, including high hardness, melting point, incompressibility, cost efficiency, and greater magnetization than iron oxides, another class of magneto-ionic target materials. ,, Iron nitrides also span a wide range of mechanical and magnetic properties, which can be tuned by varying the nitrogen concentration in Fe x N y , and can be easily integrated with semiconductor electronics.…”
Section: Introductionsupporting
confidence: 70%
“…The slightly weaker Co-O bond in CoO compared with Co3O4 also indicates that, under equivalent applied voltages, O magneto-ionics is faster in CoO than in Co3O4. [54][55][56] Fig. 3 Time evolution of (a) the saturation magnetization (MS) and (b) the coercivity (HC) for the various cobalt oxide film thicknesses with a zoom in corresponding to the first hour of time evolution of HC.…”
Section: Resultsmentioning
confidence: 99%
“…( 1) and (2). To verify the results, the calculated cohesive energies were compared with the available experimental data 24,80,[82][83][84][85][86][87][88][89] (Table S1 in the SI). The differences between calculated and experimental cohesive energies are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%